Earnings Management: Company Growth, PSAK 71, and Audit Quality with Good Corporate Governance as Moderation - Ramadhany, Nerisha Putri; Nawirah, Nawirah (Akuisisi : Jurnal Akuntansi, 2024)
This research was conducted to determine the effect of company growth, PSAK 71 regarding allowance for impairment losses (CKPN), and audit quality on profit management with good corporate governance as moderating variables. This quantitative research uses secondary data from financial reports of banking companies listed on the IDX. The sample used was 40 companies obtained using the purposive sampling technique. The data analysis technique used in this research is Moderated Regression Analysis (MRA), which is processed using the Eviews application. The results of this research conclude that Company Growth and PSAK 71 do not significantly affect Profit Management. Meanwhile, Audit Quality has a significant negative effect on Profit Management. GCG cannot moderate the influence of Company Growth on Profit Management. GCG cannot moderate the influence of PSAK 71 on Earnings Management. GCG can moderate the influence of Audit Quality on Profit Management.